Correction: Santa-Marina et al. Maternal Ferritin Levels during Pregnancy and ADHD Symptoms in 4-Year-Old Children: Results from the INMA-INfancia y Medio Ambiente (Environment and Childhood) Prospective Birth Cohort Study. Int. J. Environ. Res. Public Health 2020, 17, 7704 - Santa-Marina, Loreto; Lertxundi, Nerea; Andiarena, Ainara; Irizar, Amaia; Sunyer, Jordi; Molinuevo, Amaia; Llop, Sabrina; Julvez, Jordi; Beneito, Andrea; Ibarluzea, Jesús; Imaz, Liher; Ferrin, Maite (International journal of environmental research and public health, 2021)
In the original article [...]